KETIDAKEFEKTIFAN PENCEGAHAN PERNIKAHAN DINI DI INDONESIA: ANALISIS SISTEM HUKUM LAWRENCE M. FRIEDMAN - Muhammad Affan; Muhammad Zainuddin Sunarto (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the effectiveness of efforts to prevent early marriage in Indonesia, which remains a serious problem due to its impact on social, health, educational, and child rights protection aspects. Although the government has implemented regulatory reforms through revisions to the Marriage Law and strengthened prevention policies, the practice of child marriage continues to occur in various regions. The analysis was conducted using Lawrence M. Friedman's Legal System Theory perspective, which emphasizes the relationship between legal substance, legal structure, and legal culture. This study is a normative legal study with a conceptual approach supported by a literature review of primary legal materials in the form of relevant laws and regulations, as well as secondary legal materials in the form of scientific literature, journals, and official reports. Data were analyzed qualitatively and prescriptively by assessing the alignment between legal norms, the performance of law enforcement agencies, and the condition of the legal culture of society. The results of the study indicate that the legal substance has developed progressively through the establishment of a minimum age for marriage and supporting regulations. However, the effectiveness of its implementation is still hampered by weaknesses in the legal structure, particularly in the inconsistent practice of granting marriage dispensations, as well as the legal culture of society that still tolerates early marriage. The lack of synchronization of these three elements has resulted in prevention efforts not being optimal